The drugs phenomenon from the perspective of nursing students: patterns of consumption, attitudes and beliefs - Luciana de Souza Pereira de Magalhães; Taís Verônica Cardoso Vernaglia; Flávia Abrahão Marcolan de Souza; Silvana Vieira da Chagas; Marcelo Santos Cruz (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To describe and analyze patterns of drug use and abuse of first- and fifth-year undergraduate nursing students and to investigate their attitudes and beliefs regarding drugs and users. Method: A quantitative, descriptive and cross-sectional study of 160 students from the Federal University of the State of Rio de Janeiro was performed. Participants were interviewed using the instruments: ASSIST and NEADA FACULTY SURVEY. Collected data were analyzed with significance being set for p-values < 0.05. Results: Students of the first and the fifth years reported that alcohol had been the most frequently used drug in the previous three months (69.4% and 80.0%, respectively). Students believe they have adequate basic education about drugs however they present a prejudiced view and negative attitudes toward users. Conclusion: The pattern of drug use among students and the lack of education about the care of drug users reinforce the need to review and reformulate course contents and practices on the subject.